PENGARUH RASIO CAMEL TERHADAP RETURN SAHAM PADA BANK BUKU 3 DI INDONESIA - Nurazizah Nurazizah; Maryana Maryana; Neo Agustina (LPPM STIE Lhokseumawe, 2017)
The purpose of this study was to determine the effect CAMEL ratio consisting of CAR, NPL, BOPO, ROA and LDR to Stock Return in bank BUKU 3 in Indonesia 2010-2013. The population in this study are all the banks that are included in the category BUKU 3 of 15 conventional commercial banks. The sample was determined by purposive sampling technique in order to obtain a sample in accordance with predetermined criteria. The sample in this study, there are 8 conventional commercial bank. Analyzer used multiple linear regression. The results of analysis show that the CAR, NPL, BOPO, ROA and LDR partially no effect on Stock Return bank BUKU 3 in Indonesia, meaning H1, H2, H3, H4 and H5 rejected. Simultaneously CAR, NPL, BOPO, ROA and LDR no effect on Stock Return bank BUKU 3 in Indonesia, meaning H6 rejected.